Effect of laser radiation on catalytic properties of silicon electrodes covered with a transition metal film and providing water decomposition - Primachenko, V.E.; Fedorenko, L.L.; Tsyrkunov, Yu.A.; Zinio, S.A.; Kirillova, S.I.; Chernobai, V.A.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Current creation caused by water decomposition Н₂О → ОН+Н has been investigated for the case of an Yb-Si electrode pair after the preliminary covering of Si electrodes with transition metal (Ni, Ti, Cr) films, as well as exposing them to laser radiation. It has been shown that laser radiation, as a rule, increases the efficiency of current creation owing to the improvement of electrode catalytic properties as to water decomposition. We observed also some change in the electron work function for these electrodes